2021
DOI: 10.1016/j.medin.2020.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology and outcome of severe lower respiratory tract infections among critically ill children admitted to the PICU

Abstract: Objective: To determine the viral etiology of severe lower respiratory tract infections (LRTIs), their clinical significance and prognosis among critically ill children. Design: A prospective descriptive study was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…The local epidemiology of these combinations may differ depending on the location, climate, and season. For example, RSV and hBoV or in uenza and hBoV were reported to be the most common combinations in children with ALRI in the United Kingdom (56,57). The current study demonstrated no signi cant differences in the in-hospital mortality and length of hospitalisation between the patients detected with one virus and those with two or more viruses.…”
Section: Discussioncontrasting
confidence: 41%
“…The local epidemiology of these combinations may differ depending on the location, climate, and season. For example, RSV and hBoV or in uenza and hBoV were reported to be the most common combinations in children with ALRI in the United Kingdom (56,57). The current study demonstrated no signi cant differences in the in-hospital mortality and length of hospitalisation between the patients detected with one virus and those with two or more viruses.…”
Section: Discussioncontrasting
confidence: 41%
“…29 ARDS developed in 28.6% of the patients hospitalized in the PICU with a diagnosis of viral LRTI, and it was the most common complication among the patients hospitalized with viral infection. 30 In our study, the ratio of ARDS development was 9.4% in PCR-positive patients hospitalized in PICU with LRTIs.…”
Section: Discussionmentioning
confidence: 46%
“…In fact, the utility of FARPT in this indication is mainly epidemiological with a role of sanitary veil [35]. It has been published that the presence of a viral co-infection in bronchiolitis hospitalized in PICU can have a prognostic interest [36] but in this study, viral identification had no impact on the mortality rate. Regarding pneumonia, it would be interesting to study the real influence of PCR tests in the management of pneumonia in PICU.…”
Section: Discussionmentioning
confidence: 65%